2001
DOI: 10.1002/1096-8628(2001)9999:9999<::aid-ajmg1170>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Clinical expression and SRY gene analysis in XY subjects lacking gonadal tissue

Abstract: In several syndromes genetic males lack gonadal tissue. A range of phenotypes are seen, which varies from complete female external genitalia to anorchic subjects with sexual infantilism. Differences in phenotypic expression depend on the stage at which testes degenerated during intrauterine development. Although most cases of these syndromes are sporadic, several instances of familial recurrence suggest a genetic origin. To help elucidate the source, we performed molecular analysis of the complete SRY gene ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
(33 reference statements)
0
3
0
1
Order By: Relevance
“…4,17,[25][26][27] In our study, surgery and histological studies always confirmed the diagnosis of bilateral anorchia both in Group A and Group B patients. Although molecular defects have not yet been identified, 16,25,[28][29][30] familial cases of anorchia 1,6,10,11-13 and associated congenital malformations 2,14 have been previously reported suggesting that genetic and/or environmental factors may play an important role in the pathogenesis of anorchia. However, genetic and mechanical causes are not mutually exclusive and the pathogenesis of bilateral congenital anorchia may also be heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…4,17,[25][26][27] In our study, surgery and histological studies always confirmed the diagnosis of bilateral anorchia both in Group A and Group B patients. Although molecular defects have not yet been identified, 16,25,[28][29][30] familial cases of anorchia 1,6,10,11-13 and associated congenital malformations 2,14 have been previously reported suggesting that genetic and/or environmental factors may play an important role in the pathogenesis of anorchia. However, genetic and mechanical causes are not mutually exclusive and the pathogenesis of bilateral congenital anorchia may also be heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of this study, the molecular mechanisms of testicular regression syndrome (TRS) were not known, and no one had found evidence of association of TRS with Y‐chromosome rearrangement or with mutations of the SRY gene (Kennerknecht et al, 1993; Zenteno et al, 2001). In this study, we did not find mutations in the SRY gene other than its duplication.…”
Section: Discussionmentioning
confidence: 99%
“…Most familial cases are inherited in an autosomalrecessive or X-linked pattern, probably due to anomalies in WT1 or in other genes involved in development [9]. No defect in the SRY gene has been observed as the cause of this syndrome [10]. Agonadism may be associated with other syndromes, such as PAGOD (acronym of hypoplasia of the lung and pulmonary artery, agonadism, omphalocele/diaphragmatic defect, dextrocardia) [11][12][13]; Kennerknecht syndrome [14,15]; Seckel syndrome [16]; and CHARGE association [17].…”
Section: True Agonadismmentioning
confidence: 99%